2013
DOI: 10.4161/gmic.25487
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium infantis35624 modulates host inflammatory processes beyond the gut

Abstract: Certain therapeutic microbes, including Bifidobacteria infantis (B. infantis) 35624 exert beneficial immunoregulatory effects by mimicking commensal-immune interactions; however, the value of these effects in patients with non-gastrointestinal inflammatory conditions remains unclear. In this study, we assessed the impact of oral administration of B. infantis 35624, for 6‒8 weeks on inflammatory biomarker and plasma cytokine levels in patients with ulcerative colitis (UC) (n = 22), chronic fatigue syndrome (CFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
260
2
21

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(287 citation statements)
references
References 52 publications
4
260
2
21
Order By: Relevance
“…In another short-term study, B. longum subsp. infantis 35 624 administered to UC patients for 6 weeks resulted in a significant reduction in C-reactive protein and a non-statistically significant reduction in IL-6 when compared with the baseline [70]. While this study indicated a decrease in inflammatory markers, no clinical outcomes were measured and therefore it is not possible to conclude that this strain is effective in the treatment of UC.…”
Section: Key Questionscontrasting
confidence: 43%
“…In another short-term study, B. longum subsp. infantis 35 624 administered to UC patients for 6 weeks resulted in a significant reduction in C-reactive protein and a non-statistically significant reduction in IL-6 when compared with the baseline [70]. While this study indicated a decrease in inflammatory markers, no clinical outcomes were measured and therefore it is not possible to conclude that this strain is effective in the treatment of UC.…”
Section: Key Questionscontrasting
confidence: 43%
“…All of these probiotics are regarded as "good" bacteria, presumably inhibiting the growth of harmful bacteria or pathogens and/or improving the immune system. [67][68][69] These probiotics were also found to reduce the symptoms of gastrointestinal disease, such as irritable bowel syndrome. 15,16,58,70 Probiotics may play an important role in gut-brain axis communication, thereby benefiting both the brain and the gut.…”
Section: Effects Of Probioticsmentioning
confidence: 99%
“…There also are a limited number of studies demonstrating that supplementation with certain probiotics significantly reduced hs-CRP levels in adults that were healthy [59], pregnant [60], critically ill [61] or had inflammatory bowel disease [62] as well as other inflammatory disorders (e.g., ulcerative colitis, chronic fatigue syndrome and psoriasis) [63] and type 2 diabetes [64], suggesting that they could have a widespread anti-inflammatory effect that is clinically relevant. Considerable heterogeneity exists in the clinical trial design published to date making it difficult to determine the exact dosing and strains of probiotics needed to ensure maximal therapeutic benefits in specific clinical conditions including inflammatory disease.…”
Section: Clinically Meaningful Effects On Inflammation?mentioning
confidence: 99%